Effect of Excitation Vibration at Different Frequencies on Pick Cutting - Luo, Chenxu; Zeng, Jiawei; Gao, Junhao; Qiao, Junbei; Leng, Junfa (International Journal of Natural Resources and Environmental Studies, 2024)
The pick vibration model was established and analyzed, and discussed the influence of vibration at different frequencies on the cutting load. Then a discrete element model of the interface coal seam is established in EDEM to analyze the change of cut load at different vibration frequencies. The conclusion shows that it is more suitable to apply high frequency vibration when the coal seam content is high, and it is more suitable to apply low frequency vibration when the rock layer content is more.